2015
DOI: 10.1007/s00335-015-9559-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynonymous polymorphisms in PLA2G7 gene are associated with the risk of coronary heart disease in a southern Chinese population

Abstract: Lipoprotein-associated phospholipase A2 (Lp-PLA2) plays an important role in coronary heart disease (CHD). This study was aimed to investigate the associations of polymorphisms (R92H, V279F, I198T, and A379V) in PLA2G7 with CHD. A total of 322 patients with CHD and 414 CHD-free controls were included in the study. Polymorphisms in PLA2G7 were sequenced by DNA Sequencer and statistical analyses were performed to study the associations between polymorphisms and CHD. RH + HH genotype, RH genotype, and H allele of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Similar to other polymorphisms in PLA2G7 , the results of the correlation research on this allele in vascular disease are still complicated. Hong et al found that the T198 allele would not affect the risk of CHD in a Chinese population (OR = 1.26, 95% CI: 0.85‐1.87). Likewise, Ferguson et al failed to uncover a significant association between the I198T polymorphism and coronary artery calcification (CAC).…”
Section: Genetic Variability and Regulation Of Expressionmentioning
confidence: 68%
See 2 more Smart Citations
“…Similar to other polymorphisms in PLA2G7 , the results of the correlation research on this allele in vascular disease are still complicated. Hong et al found that the T198 allele would not affect the risk of CHD in a Chinese population (OR = 1.26, 95% CI: 0.85‐1.87). Likewise, Ferguson et al failed to uncover a significant association between the I198T polymorphism and coronary artery calcification (CAC).…”
Section: Genetic Variability and Regulation Of Expressionmentioning
confidence: 68%
“…Similar to other polymorphisms in PLA2G7, the results of the correlation research on this allele in vascular disease are still complicated. Hong et al 103 CHD (OR = 1.51, 95% CI: 1.23-1.97). Although these studies were carried out in different populations, the clearly opposing results highlight the need for further investigations to elucidate whether this genetic variant is associated with the risk and outcome of CVD.…”
Section: Ile198thr Mutation (Rs1805018)mentioning
confidence: 97%
See 1 more Smart Citation
“…Abnormally expressed PLA2G7 may give rise to dysregulation of phospholipid metabolism. PLA2G7 gene has been widely studied as a candidate risk factor of coronary heart disease [ 67 , 68 ]. Only a few reports endeavored to explore the potential roles of PLA2G7 in neurophysiological processes and pathological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54][55][56][57] Few other studies show V279F, R92H, A379V, D166E to be having a frank cardiovascular disease (CVD) risk. 54,[58][59][60][61][62][63][64][65]…”
Section: Spla 2 Mutations and Coronary Artery Diseasesmentioning
confidence: 99%